Open-data-driven embeddable quality management services for map-based web applications - Noskov, Alexey; Zipf, Alexander (Big earth data, 2018)
Various map-centered web services facilitate citizens’ lives. Web-map applications exist for many years already. Due to simplification and improvement of technologies supporting WebGIS, map-based services become more popular and important nowadays. Data quality assurance for such services is a significant challenge. Since many of such applications intensively use open data, approaches focused on open solutions are required. This work proposes a data-quality concept, which is based on intrinsic and comparable approaches. OpenStreetMap (OSM) allows intrinsic data evaluation. Moreover, it is used as a reference dataset for quality assessment of public-sector-information Open Data layers. Equidistant point (EDP)-based statistics enables to filter out low-quality Open Data features. A data-type model carries out the inventory of OSM data. The comparison of raster web-map tile file sizes and calculation of a simplified data quality indicator make it possible to specify acceptable data quality levels. Embeddable instances of quality assurance web services incorporate data features with acceptable quality. This work provides all required software and data for the deployment of such services under liberal licenses. Concrete instructions allow users to adopt the proposed solutions for their platforms. Some generic use cases illustrate the advantages of the introduced shared web services.
Online veröffentlicht: 5. April 2019
Gesehen am 19.02.2026